"Influential knowledge and financial performance: The role of time and rivals' absorptive capacity". (April 2021) - Papazoglou, Michalis E.; Spanos, Yiannis E.
Abstract: There is a general consensus among scholars that knowledge is probably the most important source of competitive advantage. The influential, novel knowledge incorporated in patented inventions can be considered as a valuable resource for firms. The research questions that are at the heart of this work are how long the effect of influential knowledge on financial performance can last and how this effect interacts with rivals' absorptive capacity. We test our hypotheses on longitudinal data from the chemical industry. Our findings suggest that influential patented knowledge has a negative, though weak, effect on financial performance in the first year after patent application, but the effect becomes strongly positive in the second year, even though it lasts only for one year. Moreover, contrary to our expectations, we find that the effect of influential knowledge on financial performance is positively moderated by rivals' absorptive capacity. Highlights: Influential knowledge can be considered as a valuable but imitable resource. We focus on the duration of the impact of influential knowledge on profitability. The positive effect of influential knowledge on profitability is short-lived. Rivals' absorptive capacity positively moderates this effect.